The industrial policies and their role in the development of the manufacturing sector in Syria (Damascus University Journal for the economic and Political sciences, 2025)
The research presents the reality of industrial policy and manufacturing industry in Syria, as it focuses on the extent of The importance of industrial policies and the role they play in the development of the manufacturing sector in Syria, and the research seeks to study and present the most important results related to the reality of industrial policies, their effectiveness and their role in developing the manufacturing sector in Syria, industrial policies have gained wide support in recent years as an effective approach to overcoming the state of market failure, and the research stems from a basic premise that industrial policy has a positive impact and importance The research concludes with several results and proposals, the most important of which is that despite the role played by industrial policies in developing the manufacturing sector in Syria, the contribution of this sector to the Syrian economy did not reach the level that is commensurate with the importance of this sector, which It reflects the necessity of adopting a modern industrial policy to modernize the manufacturing sector in Syria, which would raise this sector to a higher level, efficiency and greater competitiveness, adopt green industrial policies and environmentally friendly practices, and provide the necessary technical support for industrial institutions wishing to develop their products and use modern technologies and technology.
Keywords: Industrial Policy; Manufacturing Industry; Industrial Development.